2016
DOI: 10.1080/14647273.2016.1196296
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pregnancies following discontinuation of IVF/ICSI treatment: an internet-based survey

Abstract: The objective was to determine the likelihood of conceiving spontaneously following cessation of IVF/ICSI; how long does it take and what factors are associated with conception? The design was an internet-based survey. All registered users of www.ivf-infertility.com received an electronic questionnaire addressing issues relating to the duration and cause of infertility, number of IVF/ICSI cycles and outcome, whether they conceived following cessation of IVF/ICSI and the time taken to conceive and outcome. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Another study, which included 7 to 9 years of follow up time, reported a cumulative live birth rate of 17% after a prior successful IVF/ICSI [8]. Further, an internet survey study included varying times of follow up and reported 27.3% spontaneous conception rate after successful IVF/ICSI [7]. This particular study, however, may be an overestimation of the true rate, as those women who did conceive are conceivably more likely to respond to the online survey.…”
Section: Infertility and Spontaneous Conceptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another study, which included 7 to 9 years of follow up time, reported a cumulative live birth rate of 17% after a prior successful IVF/ICSI [8]. Further, an internet survey study included varying times of follow up and reported 27.3% spontaneous conception rate after successful IVF/ICSI [7]. This particular study, however, may be an overestimation of the true rate, as those women who did conceive are conceivably more likely to respond to the online survey.…”
Section: Infertility and Spontaneous Conceptionmentioning
confidence: 99%
“…Few studies can be identified that assess spontaneous conception rates after failed ART treatments. The internet study mentioned previously also analyzed spontaneous conceptions among women who had unsuccessful IVF/ICSI treatments and decided to discontinue treatments [7]. The authors report that 35.4% of these women achieved spontaneous conception.…”
Section: Infertility and Spontaneous Conceptionmentioning
confidence: 99%
See 3 more Smart Citations